Heparin, heparan sulfate and heparanase in inflammatory reactions - Li, Jin-ping; Vlodavsky, Israel (Thrombosis and Haemostasis, 2009)
Heparan sulfate (HS) proteoglycans at the cell surface and in the extracellular matrix of most animal tissues are essential in development and homeostasis, and are implicated in disease processes. Emerging evidence demonstrates the important roles of HS in inflammatory reactions, particularly in the regulation of leukocyte extravasation. Heparin, a classical anticoagulant, exhibits anti-inflammatory effects in animal models and in the clinic,presumably through interference with the functions of HS, as both polysaccharides share a high similarity in molecular structure. Apart of regulation during biosynthesis, the structures of HS and heparin are significantly modulated by heparanase, an endoglycosidase that is upregulated in a number of inflammatory conditions. Exploring the physiological roles of HS and heparin and the mode of heparanase action in modulating their functions during inflammation responses is of importance for future studies.
Keywords: Polysaccharide; proteoglycans; structure/function; chemokine; vascular endothelium; transmigration